EVALUATION OF THE INSTALLATION AND ACTIVATION OF AIS AND COMMUNICATION DEVICES ON TRADITIONAL MOTOR SHIP ON THE SIMANINDO – TIGARAS TRAFFIC, NORTH SUMATERA PROVINCE - Khairani, Muhammad; Sari, Yulia Puspita; Priyono, Broto; Bokau, Joe Ronald Kurniawan; Ulya, Febriyanti Himmatul; Febriansyah, Febriansyah (IWTJ : International Water Transport Journal, 2024)
Simanindo Port is a very important ferry port in connecting Sumatra Island with Samosir Island via waterways. In this case, the author compares the installation and activation of AIS and communication devices, but the current conditions are not in accordance with the Regulation of the Minister of Transportation Number PM 18 of 2022 concerning the Automatic Identification System for Ships Carrying Out Activities in the Territory of Indonesia and the Regulation of the Director General of Land Transportation Number: KP.3424 / AP.402 / DRJD / 2020 concerning River and Lake Ships. Through qualitative methods, the author conducted direct observations of the actual conditions in the field, namely seeing directly the operation of traditional motorboats, boarding and disembarking passengers and AIS installed on traditional motorboats and their activation while the ship was sailing. Based on the analysis results that have been obtained, the KSOPP Lake Toba together with the Water Police and the government have made efforts so that ship operators comply with the installation and activation of AIS and communication devices to support smooth sailing of ships, namely by carrying out ramp checks and coaching for ship operators who are not yet compliant. But in reality, of the 17 traditional motor ships operating, there are still 2 traditional motor ships that have not been installed with AIS, 6 traditional motor ships that have not been installed with communication devices and on each ship that has been installed with AIS and communication devices, it is still not effective in terms of activation when sailing and tends to deactivate AIS and the communication device. So ship owners need to be aware of installing AIS and communication devices on ships and ship operators must also always activate AIS when sailing for shipping safety.